Efektivitas Model Pembelajaran Search, Solve, Create, Share (SSCS) Terhadap Prestasi Matematika - Wicaksono, Bintang (Program Studi Pendidikan matematika STKIP PGRI Pacitan STKIP PGRI Pacitan, 2024)
The low learning achievement of students is likely caused by students' difficulties in understanding the material and lack of motivation in learning. This can occur due to the learning being implemented not being in accordance with the characteristics of the students in the class. So it is necessary to look for new learning solutions that suit student characteristics. This research aims to determine the effectiveness of the Search, Solve, Create, and Share (SSCS) learning model on student learning achievement in class X of Al-Furqon Sanden IT Vocational School. The samples used were class X Culinary Arts with 25 students (Control class) and class The type of research used is quasi-experimental with a research design in the form of a Posttest Control Group Design. In this design, a posttest is given to both groups after being given treatment. Based on posttest data analysis, the results of the sig t-test value (2-tailed) show that the sig. (0.152/2) > 0.05, then ????0 is accepted and ????1 is rejected. So it can be concluded that the SSCS model has no effect on the effectiveness of mathematics learning. The results of the statistical group hypothesis test show that the average value in the control class is higher than the average value in the experimental class. However, the results of hypothesis testing using statistics showed that the SCSS learning model had no effect (significantly) on students' mathematics learning achievement. Keywords: Effectiveness; Search Solve Create and Share (SSCS) learning model; learning achievement.